Mother's Behavior Regarding MP-ASI and Nutritional Statusin Infants Aged 6-24 Months in the Working Area of the Marisa Health Center - Tiara Monoarfa; Sunarto Kadir; Agusrianto Yusuf (LPPM Universitas Bina Mandiri Gorontalo, 2023)
Mother's behavior in providing complementary feeding, both in terms of timeliness, type of food, and amount of food is determined by the mother's knowledge of complementary foods for breast milk. The formulation of the problem in this study is how the behavior of mothers regarding the provision of complementary feeding and nutritional status in infants aged 6-24 months. This study aims to determine the mother's behavior in providing complementary feeding and nutritional status of infants aged 6-24 months. This study uses descriptive qualitative research methods. The population in this study were 124 mothers who had babies. In this study, samples were taken as many as 95 people using the Slovin formula. The type of data used is primary data sourced from interviews. The data analysis technique used in this research is the analytical descriptive method, which describes the data collected in the form of words, pictures and not numbers. The results showed that the mother's knowledge was good at 21.05%, sufficient knowledge was 29.47% and most of them had less knowledge at 49.48%. Mother's attitude towards complementary feeding has a good attitude of 44.21% and a bad attitude that is 55.79%. The mother's practice of giving complementary foods to breast milk has a good practice of 38.94% and a bad practice of 61.05%. Nutritional status of children under the age of 6-24 months shows that they are fat at 4.21%, normal is 34.74% and most of them are malnutrition as much as 61.05%.